Isu Pendidikan Islam Di Era Global - Difa’ul Fikri Jayyid; Sukari (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the concepts, challenges, impacts, and opportunities regarding Islamic education in the global era. Employing a qualitative approach via library research, data were gathered through the documentation of literature sources and analyzed using an interactive model. The findings indicate that the concept of Islamic education must integrate spiritual values with the demands of modernity. Key challenges include adolescent identity crises, educators' limited digital competence, and the requirements for 21st-century skills. Although it has triggered commercialization and cultural erosion, globalization has also had positive impacts, such as expanded access to knowledge and innovations in digital learning methods. In conclusion, globalization presents strategic opportunities for the integration of contemporary knowledge, techno-pedagogical digitalization, and the reconstruction of a "glocal" identity. Consequently, Islamic educational institutions need to collaboratively revitalize their curricula to produce graduates who are globally competitive yet possess noble character. Penelitian ini bertujuan menganalisis konsep, tantangan, dampak, serta peluang pendidikan Islam di era global. Menggunakan pendekatan kualitatif dengan metode library research , data dikumpulkan melalui teknik dokumentasi sumber pustaka dan dianalisis menggunakan model interaktif. Hasil penelitian menunjukkan konsep pendidikan Islam harus mengintegrasikan nilai spiritual dengan tuntutan modernitas. Tantangan utamanya meliputi krisis identitas remaja , rendahnya kompetensi digital pendidik , dan tuntutan kecakapan abad ke-21. Meskipun memicu komersialisasi dan erosi budaya , globalisasi berdampak positif pada perluasan akses ilmu serta inovasi metode pembelajaran digital. Kesimpulannya, globalisasi membuka peluang strategis bagi integrasi ilmu kontemporer , digitalisasi teknopedagogis , dan rekonstruksi identitas glokal. Implikasinya, institusi pendidikan Islam perlu merevitalisasi kurikulum secara kolaboratif agar menghasilkan lulusan yang kompetitif secara global namun tetap berakhlak mulia.